Marketing of Library and Information Services in Nigerian University Libraries: An Entrepreneurial Perspective - Grace Effiong Etukudo; Luqman Ayanlola Atanda (Newinera Publisher, 2022)
This paper discussed the marketing of library and information services vis-Ã -vis entrepreneurial activities in the library with particular reference to the academic libraries. The information age, which revolutionized all human activities including the library and information services and also the ICT incursion made marketing of library and information services and the inclusion of entrepreneurial activities necessary if librarianship must thrive among its competitors in the business of human management and provision. Marketing concepts, with particular reference to the 7Ps in â€œmarketing mixâ€ are highlighted. The paper worked on secondary data using the Narrative Textual Case Study (NTCS) and some discussions with professional colleagues in the field of librarianship to draw some valid conclusions.